Molecular Taxonomy of Conogethes punctiferalis and Conogethes pinicolalis (Lepidoptera: Crambidae) Based on Mitochondrial DNA Sequences - Jing WANG; Tian-tao ZHANG; Zhen-ying WANG; Kang-lai HE; Yong LIU; Jing LI (Journal of Integrative Agriculture, 2014)
Conogethes punctiferalis (Guenée) (Lepidoptera: Crambidae) was originally considered as one species with fruit-feeding type (FFT) and pinaceae-feeding type (PFT), but it has subsequently been divided into two different species of Conogethes punctiferalis and Conogethes pinicolalis. The relationship between the two species was investigated by phylogenetic reconstruction using maximum-likelihood (ML) parameter estimations. The phylogenetic tree and network were constructed based upon sequence data from concatenation of three genes of mitochondrial cytochrome c oxidase subunits I, II and cytochrome b which were derived from 118 samples of C. punctiferalis and 24 samples of C. pinicolalis. The phylogenetic tree and network showed that conspecific sequences were clustering together despite intraspecific variability. Here we report the results of a combined analysis of mitochondrial DNA sequences from three genes and morphological data representing powerful evidence that C. pinicolalis and C. punctiferalis are significantly different.